Peran Pegadaian Syariah Dalam Meningkatkan Kesejahteraan Masyarakat Di Era Digital - Alfiyah, Anis Nur; Putri, Anisa; Rahmadanis, Intan Aulia; Aprilliana, Meliza Eno; Yuriantika, Silvia; Muhadis, Tengku (Universitas Muhammadiyah Sumatera Utara, 2025)
The development of digital technology presents both challenges and opportunities for Islamic financial institutions, including Islamic Pawnshops (Pegadaian Syariah), to expand their service reach and effectiveness. This study aims to explore the role of Islamic Pawnshops in enhancing community welfare in the digital era, particularly through service digitalization, sharia-based financing, and financial education. This research adopts a qualitative method with a literature review approach, gathering data from various relevant sources. The findings indicate that Islamic Pawnshops serve as a fair and inclusive financial solution, especially for lower-middle-income communities. Through services such as Rahn (Islamic pawn), micro-enterprise financing, gold savings, and digital applications, Islamic Pawnshops play a significant role in supporting economic growth, increasing financial literacy, and promoting the use of sharia-compliant financial technology. Therefore, Islamic Pawnshops have great potential in creating a more prosperous and empowered society in the era of digital transformation.